(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study was to assess how learning resources and motivation affect accounting learning outcomes at SMK Negeri 1 Semende Darat Laut. This study used quantitative methodology with a descriptive correlational design. Questionnaires measuring learning facilities, learning motivation, and learning achievement were used to collect data from the sample, which included 35 accounting students in grade XI. The results of multiple linear regression analysis showed that learning motivation and learning facilities significantly improved accounting learning achievement. A comfortable classroom setting, easy access to resources, and additional technology are examples of good learning facilities that can improve the efficiency of the learning process. On the other hand, learning motivation, both intrinsic and extrinsic, encourages students to participate more actively and enthusiastically in learning, which has an impact on increasing their achievement. This research concludes that improving learning facilities and learning motivation are key factors in improving accounting learning outcomes in vocational schools. Therefore, schools are advised to continue to improve existing facilities and formulate strategies to stimulate students to be more motivated in learning.